Pengaruh Intradialytic Exercise terhadap Tingkat Kecemasan pada Pasien Gagal Ginjal Kronik di Ruangan Hemodialisa RSUD Kota Tanjungpinang - Yopy Octaviana Hasibuan; Mira Agusthia; Rachmawaty M. Noer (Pusat riset dan Inovasi Nasional, 2025)
Chronic kidney failure is a pathophysiological condition that can arise due to various etiologies. Hemodialysis patients with chronic kidney failure who experience problems and clinical difficulties can affect anxiety levels, one of the non-pharmacological treatments that can be given to patients is Intradialytic exercise because the movements are simple, do not interfere with the hemodialysis procedure, and are useful in reducing anxiety levels. This study aims to determine the effect of intradialytic exercise on anxiety levels in patients with chronic kidney failure in the hemodialysis room of Tanjungpinang City Hospital. This study uses a quantitative research method with a quasi-experimental design without control design, the design form used is pre and post test. The sample in this study of patients treated at Tanjungpinang City Hospital amounted to 30 people with random sampling techniques. The anxiety level measurement instrument uses the Hamilton Anxiety Rating Scale (HARS) questionnaire. The statistical analysis used was a normality test with a sig value. > 0.005, t paired sample t test and independent t test. There was a significant influence between the average anxiety level score at the pre-test and post-test in the intervention group (intradialytic exercise) (mean pre-test = 24.60 to mean post-test = 18.33) with a p-value of 0.000. Conclusion this study found the effect of intradialytic exercise on anxiety levels in patients with chronic kidney failure in the hemodialysis room of Tanjungpinang City Hospital. Suggestion for Tanjungpinang City Hospital, intradialytic exercise therapy can be considered as a non-pharmacological management in patients with chronic kidney failure in the Hemodialysis room to reduce anxiety levels